Intelligent Anti-Theft Finding Scheme Towards iTrust Establishment in Delay Tolerant Networks Using VANET - Swetha, Bhogapathi; Bulla Rao, D; Nageswara Rao, P (International Journal of Computer Sciences and Engineering, 2014)
Malicious and selfish behaviors represent a serious threat against routing in Delay/Disruption Tolerant Networks (DTNs). Due to the unique network characteristics, designing a misbehavior detection scheme in DTN is regarded as a great challenge. In this paper, we propose iTrust, a probabilistic misbehavior detection scheme, for secure DTN routing towards efficient trust establishment. The basic idea of iTrust is introducing a periodically available Trusted Authority (TA) to judge the node’s behavior based on the collected routing evidences and probabilistically checking. A new VANET-based smart parking scheme (SPARK) for large parking lots provide three convenient services for drivers: 1) real-time parking navigation; 2) intelligent anti-theft protection; and 3) friendly parking information dissemination. TA could ensure the security of DTN routing at a reduced cost. To further improve the efficiency of the proposed scheme, we correlate detection probability with a node’s reputation, which allows a dynamic detection probability determined by the trust of the users. The extensive analysis and simulation results show that the proposed scheme substantiates the effectiveness and efficiency of the proposed scheme.